THE IMPORTANCE OF COORDINATION BETWEEN INTERNAL AND EXTERNAL AUDIT IN THE ADMINISTRATIVE PROCESS - Masnawaty Sangkala (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The coordination between internal and external auditors is crucial in carrying out their professional duties and responsibilities. This coordination process involves exchanging information, sharing audit opinions, as well as discussing audit planning and reporting. The study is focused on assessing the significance of internal audit alignment and the interaction between internal and external audit. The research method employed is an empirical study with a quantitative approach through surveys and in-depth interviews with internal and external auditors in various industrial sectors. The findings indicate that effective coordination between internal and external auditors can prevent job duplication, enhance the accuracy and reliability of financial reports, and improve operational efficiency of the company. The research discussion emphasizes the importance of support from management as auditee in the audit process and the need to maintain the independence of internal auditors for audit effectiveness. The research gap lies in the lack of in-depth empirical exploration on how this coordination is implemented in practice and its impact in various organizational contexts. Therefore, this study provides a significant contribution to the understanding and practice of coordination between internal and external auditors, and offers recommendations for further research in the future.